Implementation of Student Responsibility Character in Strengthening National Assessment of Education Report Cards at SMAN 1 Pringgabaya - Aulia, Widyatul; Mustari, Mohamad; Basariah, Basariah; Alqadri, Bagdawansyah (Universitas Negeri Gorontalo, 2025)
This study aims to determine the nature of student responsibility in improving the Education Report Card at SMAN 1 Pringgabaya through national assessment. This research uses a qualitative approach with a descriptive type. This research uses purposive sampling technique, which involves interview, observation, and documentation to collect data. In addition, the data analysis technique used in this research is the interactive model, which consists of several parts, such as data reduction, data presentation, and conclusion drawing. The observation guideline sheet, interview guideline sheet, and documentation sheet explain the data collection process. The interview and observation guideline sheets are used as a reference to find out the various activities of implementing the character of responsibility of students in strengthening the results of the national assessment on the education report card. The results of data acquisition will then be reduced according to the information needed, then data display will be carried out and the last is to draw conclusions from the results of the data that has been analysed. The research results obtained after conducting several appropriate research procedures, namely the strengthening of national assessments based on the character of responsibility at SMAN 1 Pringgabaya showed a significant increase with an average achievement of 8.02%. This can be seen from the results of the school report card and various ordinary activities carried out every day, both during learning and extracurricular activities.